(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This chapter showcases some of the recent state-of-the-art research works which have been used here to form the background and base of the current work presented in the thesis. It also describes the techniques and technologies used in the current work to provide a basic overview. The review of literature is divided into two parts. The first part deals with the recent proposals and comparisons of various distributed file system architectures for handling big data in terms of storage, access mechanisms, security, privacy and reliability. The second part specifically deals with Hadoop Small Size file handling problem and the proposed solutions in recent years to overcome this problem. This chapter presents literature survey of Big Data and various clustering techniques for analyzing Big Data and tabular comparison of these techniques is presented [Zhang 2009].